2020
DOI: 10.1093/aob/mcaa083
|View full text |Cite
|
Sign up to set email alerts
|

How plant allometry influences bud phenology and fruit yield in two Vaccinium species

Abstract: Background and Aims Understanding how plant allometry, plant architecture and phenology contribute to fruit production can identify those plant traits that maximize fruit yield. In this study, we compared these variables and fruit yield for two shrub species, Vaccinium angustifolium and Vaccinium myrtilloides, to test the hypothesis that phenology is linked to the plants’ allometric traits, which are predictors of fruit production. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…This explains positive associations between yield-related traits and stem structural traits, which need further physiological studies to confirm. It was previously observed in wild blueberries that greater stem length is related to higher fruit biomass [12]. Additionally, genotypes with a higher StemL might be benefitted in terms of successful pollination by bees, which is one of the major yield determining factors of wild blueberries [46].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This explains positive associations between yield-related traits and stem structural traits, which need further physiological studies to confirm. It was previously observed in wild blueberries that greater stem length is related to higher fruit biomass [12]. Additionally, genotypes with a higher StemL might be benefitted in terms of successful pollination by bees, which is one of the major yield determining factors of wild blueberries [46].…”
Section: Discussionmentioning
confidence: 96%
“…Thus, these features can be considered the parts of a developmental module that dictates crop performance and yield; the optimization of these developmental features is essential for the efficient performance of crop plants. Genotypes of wild blueberries with a greater vegetative biomass, which is represented by several structural traits, i.e., stem height and number of leaves, can produce more flowers, which ultimately results in higher fruit biomass [12]. Plant stem height and diameter are closely related to biomass production and are important morphological traits affecting yield performance [10].…”
Section: Introductionmentioning
confidence: 99%
“…In diffuse-porous species, BAI and the number of vessels decreased in 2012, while stem elongation and the number of total ramifications decreased slightly in 2012 and more strongly in the following year, i.e., 2013. The number of shoots and lateral branches is predetermined and depends upon carbon storage of the previous year ( Fournier et al, 2020 ). We observed that the number of total ramifications strongly depends upon SPEI 3 variation during the previous year, especially in diffuse-porous species.…”
Section: Discussionmentioning
confidence: 99%
“…The first investigative model considered seasonal mean temperature, total precipitations, and number of freezing days—days with minimum mean temperature <−5 °C [ 44 ]—between April and August inclusively in vegetative and fruit-bearing years. The second investigative model considered mean temperatures and total precipitations for phenological stages described by Fournier et al [ 45 ] and presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%